Design and Development of a smart garage door system - Mohamed Ariff, M.I. (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents the design and development of a smart garage door system, which is operated by an Arduino microcontroller via the use of a mobile application and the Blynk cloud sever. Further, this mobile application allows the smart garage door to be controlled and accessed from any remote location via the use of the Blynk cloud server which is connected to the Internet using Wi-Fi or 3G/4G network. The operations of this smart garage door also function using the Google assistant voice command. Finally, this smart garage door application has been tested and it is able to successfully perform the basic operations of a smart garage door as proposed in the initial design and development stage. Â© 2022 IEEE.